Extensive sequence homology at the 3'-termini of the four RNAs of cucumber mosaic virus. - Symons, R H (1979)
The sequences of 270 residues from the 3'-termini of the four RNAs of cucumber mosaic virus have been determined by copying the in vitro polyadenylated RNAs with reverse transcriptase using d(pT8G) as primer and the 2',3'-dideoxynucleoside 5'-triphosphates as specific chain terminators. The terminal sequences of RNAs 3 and 4 were identical; this was expected since hybridization data has shown that the sequence of RNA 4 was present at the 3'-end of RNA 3 (Gould and Symons (1978) Eur. J. Biochem. 91, 269-278). The first 138 residues of RNAs 1 and 2 were identical to those of RNAs 3 and 4 except for one residue in RNA 1 and three residues in RNA 2. From residue 139 to 270 from the 3'-terminus, RNAs 1 and 2 showed, relative to RNAs 3 and 4, a non-homologous region of 33 residues, a homologous region of 40 residues, a partially homologous region of 14 residues which probably extended to about residue 300. There were 11 residues different between RNAs 1 and 2.